Study on Urine Metabolic Profile of Aβ25–35-Induced Alzheimer's Disease Using UHPLC-Q-TOF-MS. (1st December 2018) - Liu, Yuanyuan; Wei, Mengying; Yue, Kexin; Hu, Mingxin; Li, Shizhe; Men, Lihui; Pi, Zifeng; Liu, Zhiqiang; Liu, Zhongying
Highlights: An Aβ25–35-induced AD model developed on Sprague–Dawley rats was successfully established at 8 weeks after surgery. The content of 9 neurotransmitters in the hippocampus of AD rats changed significantly. 45 endogenous metabolites mainly involved in 8 metabolic pathways were identified as potential biomarkers related to AD. The pathogenesis of AD was due to gut microbiome dysbiosis, inhibition of energy metabolism and oxidative stress injury. Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder, with no effective method for its treatment so far. The pathogenesis of AD has been reported, but the endogenous metabolic profile and disease-related biomarkers are still not clear. To better understand AD, an AD model induced by injecting β-amyloid 25–35 (Aβ 25–35) solution into bilateral hippocampus was developed on Sprague–Dawley rats. After 8 weeks of modeling, the impairment of spatial learning and memory ability in AD rats were assessed by Morris water maze task. Hematoxylin and eosin staining and immunohistochemistry were used to investigate the pathological changes of hippocampus. The neurotransmitter concentrations in the hippocampus were measured using UHPLC-TQ-MS. Urinary metabolomics based on UHPLC-Q-TOF-MS was established to delineate the alterations of endogenous metabolites in AD rats. The results showed that compared with healthy control rats, AD rats suffered from cognitive dysfunction, hippocampus damage, Aβ formation and tau phosphorylation at 8 weeks after surgery, suggesting that the Aβ25–35-induced AD model was successfully established. In addition, the levels of γ-aminobutyric acid, acetylcholine, glycine, norepinephrine, serotonin, taurine and dopamine decreased and glutamate and aspartic acid increased in hippocampal tissue of AD rats. 45 altered metabolites mainly involved in 8 metabolic pathways were identified as the endogenous biomarkers of AD. According to the analysis of the biological significance of metabolic profiles, the pathogenesis of AD was mainly due to gut microbiome dysbiosis, inhibition of energy metabolism, oxidative stress injury and loss of neuronal protective substances.